Риторичне питання в системі синтаксичних одиниць української мови - Базан, Ольга; Bazan, Olha (Східноєвропейський національний університет імені Лесі Українки, 2013)
У статті досліджується проблема стратифікації риторичних питань у системі синтаксичних одиниць української мови. Риторичне питання розглянуто як універсальний функціональний тип синтаксичних одиниць, який має диференційні ознаки питальних (зовнішня питальна форма) і розповідних речень (значення повідомлення), й визначається як невласне-питальний тип питальних речень.This article embraces the issues of rhetorical space in the system of syntactic units of the Ukrainian language, in particular the establishment of their structural and semantic characteristics. Rhetorical questions are considered as a universal functional type of syntactic units which have differential features of thequestion (external form of the question) and narrative sentences (the message). Such structures form non-interrogative type of interrogative questions. The following are dominant characteristics of rhetorical questions as interrogative sentences of noninterrogative type: full-request for partial information stated or not stated; word order, availability of question components, specific intonation.
Rhetorical Questions in the System of Syntactic Units of the Ukrainian Language
Keywords: риторичне питання; заголовок; медіатекст; типи речень за метою висловлювання; розповідні речення; питальні речення; запит; rhetorical question title; heading; types of sentences from the purpose statements; narrative sentence; interrogative sentence and request